Câmara de resfriamento evaporativo de energia zero em adobe como auxiliar ao desenvolvimento sustentável de comunidades remotas - KARINE MACHADO DAVALO (2022)
The construction of evaporative coolers in remote communities can contribute to increasing the longevity of vegetables, with improved food security and the economy of small farmers in remote places, very poor or without access to electricity. This work aimed to design, build and analyze the performance of a full-scale evaporative cooler to meet the restrictive conditions of farmers in remote locations. It was conducted by the steps of Design science research (DSR), and the solution consists of a chamber that uses double adobe walls, filled with wet sand, to induce the occurrence of evaporative cooling. A 1:1 scale prototype was built, in which initial performance tests were carried out in the dry and wet states, with different volumes of water. The results show promising performance data. Stabilized adobe proved to be a good choice for use in the cooler, even though it is subject to moisture. The enlargement of the cooler internal volume, as well as the shape adopted for the cooler, demonstrated their effectiveness. As for the efficiency of evaporative cooling, although insipient, the data obtained show that the cooler, as expected, has its best performance on the hottest and driest days, reducing the temperature (up to 13.24°C difference, with an external temperature of 40.5°C and an internal temperature of 27.26°C) and manages to keep the internal humidity between 53.63% and 92.71%. Keywords: food safety, evaporation, appropriate technology, refrigerator, cooler, earthen construction.